Associations of Vestibular Tests With Penn Acoustic Neuroma Quality of Life Scores After Resection of Vestibular Schwannoma. Issue 2 (February 2020) - Brown, Clifford Scott; Cooper, Matthew W.; Peskoe, Sarah B.; Risoli, Thomas; Kaylie, David M.
Abstract : Objective: Determine associations between preoperative caloric testing and video head impulse testing (vHIT) with baseline and postoperative Penn Acoustic Neuroma Quality of Life (PANQOL) scores following resection of vestibular schwannoma (VS). Study Design: Retrospective case series. Setting: Two tertiary referral hospitals. Patients: Adult patients with unilateral VS, preoperative calorics, vHIT, and dizziness handicap inventory (DHI) score. Interventions: Surgical resection of VS and postoperative surveys. Main Outcome Measures: PANQOL scores. Results: Forty-three patients were included (58.1% women) with a median age of 54 years (range, 28–82). Mean tumor size was 14.8 mm (σ=8.6), and 28 (65.1%) were right-sided. Average preoperative vHIT gain was 0.7 (σ = 0.3). Covert and overt saccades were present in 8 (25%) and 14 (42.4%) patients, respectively. Average preoperative unilateral weakness was 47% (σ = 33.2). Translabyrinthine approach was performed in 26 (60.5%) patients. No significant difference of PANQOL scores was noted at baseline or over time between patients with normal (>0.8) or abnormal (<0.8) gain. Patients with more unilateral weakness (>50%) had significantly higher baseline PANQOL scores compared with those with < 25% or 25 to 50% ( p = 0.02), but had significant improvement in scores over time ( p = 0.01). Higher preoperative DHI preoperatively was significantly associated with worse PANQOL scores at all timepoints (β=0.57, p = 0.0064). No differences in PANQOL scores amongst surgical approaches were observed. Conclusion: Preoperative vestibular testing with vHIT, calorics, DHI, and baseline PANQOL surveys may allow for patient counseling regarding postoperative quality of life over time.